Left atrial epicardial adipose tissue is associated with low voltage zones in the left atrium in patients with non-valvular atrial fibrillation - Shao, Yameng; Chen, Lei; Chen, Wensu; Sang, Chuanyi; Xu, Changjiang; Zhang, Chaoqun (Frontiers in Cardiovascular Medicine, 2022)
Objective Epicardial adipose tissue (EAT) is related to atrial fibrillation (AF), but the specific mechanism is still unclear. Left atrial (LA) low voltage zones (LVZ) can well reflect atrial fibrosis. This study investigated the relationship between EAT and LVZ in non-valvular AF (NVAF) patients. Methods This observational study including patients with NVAF (n=214) undergoing radiofrequency ablation (RFCA) for the first time in our hospital and 62 matched controls. The EAT volume and attenuation were measured by contrast-enhanced computed tomography. A three-dimensional mapping system was used to map the left atrial endocardium and evaluate LA-LVZ. Patients were divided into LVZ and non-LVZ groups according to the presence or absence of LVZ. Results Patients with AF showed higher LA-EAT volume and lower attenuation value than controls (29.7±11.2 cm3 vs. 20.9±8.6 cm3, P=0.021; -91.2±5.6 HU vs. -88.7±5.9HU, P<0.001). Compared with the group without LVZ, there were significant differences in age (65[59-71] vs. 60[52-69], P=0.006), LAVI (75.1 ± 20.7 ml/m2 vs. 67.2 ± 20.9 ml/m2, P=0.018), LA-EAT volume (34.8 ± 11.5 cm3 vs. 28.1 ± 10.6 cm3, P<0.001) and LA-EAT attenuation (-93.9 ± 5.3HU vs. -90.4 ± 5.5 HU, P<0.001).Multivariate regression analysis showed that age(OR=1.040; 95%CI: 1.001-1.078, P=0.042), LAVI (OR=1.019; 95%CI: 1.002-1.037, P=0.032),LA-EAT volume (OR=1.193; 95%CI: 1.015-1.402, P=0.034) and attenuation value (OR=0.801; 95%CI: 0.701-0.916 P=0.001) were independent predictors of LVZ. After LA-EAT attenuation was incorporated into the clinical model, the comprehensive discrimination and net reclassification tended to improve (IDI and NRI > 0, P < 0.05). Conclusion LA-EAT volume and attenuation values can independently predict the presence of LVZ, and LA-EAT attenuation has a better predictive value than LA-EAT volume.